Deviations From μ‐τ Symmetry Using Δ27 Group on Neutrino Masses and Mixings - Ph. Wilina; N. Nimai Singh (Advances in High Energy Physics)
The implication of the neutrino mass model based on Δ27 discrete flavor symmetry, on parameters of neutrino oscillations, CP violation, and effective neutrino masses is studied using the Type I seesaw mechanism. The standard model particle content is extended by adding two additional Higgs doublets, three right-handed neutrinos, and two scalar triplets under Δ27 symmetry predicting diagonal charged lepton mass matrix. This can generate the desired deviation from μ‐τ symmetry. The resulting neutrino oscillation parameters are well agreed with the latest global fit oscillation data. The sum of the three absolute neutrino mass eigenvalues, ∑imi (i=1,2,3), is found to be consistent with the value given by the latest Planck cosmological data, ∑imi<0.12 eV. The model further predicts effective neutrino masses for neutrinoless double beta decay, 4.15 meV≤mee≤30.6 meV; tritium beta decay, 8.4 meV≤mβ≤30.5 meV; Jarlskog invariant, JCP=±0.022 for CP violation; baryon asymmetry YB=1.15×10−10 for normal hierarchical case; and also 49.5 meV≤mee≤51.7 meV, 49.5 meV≤mβ≤51.4 meV, JCP=±0.022, and YB=1.12×10−10 for inverted hierarchical case, respectively.